Alabama Course of Study Humanities, K-12. Bulletin 1983, No. 16. - Alabama State Dept. of Education, Montgomery; Alabama State Dept. of Education, Montgomery ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
A scope and sequence for incorporating humanities into the existing K-12 curriculum contains 8 sections. Following an introduction, the first section outlines characteristics of an effective humanities program. The second and third sections contain teacher and student objectives for a humanities program, minimum requirements, and alternatives for such a program. The fourth section, a chart, suggests strategies for integrating humanities themes into appropriate skill and content areas. For each grade level, specific topics, skills, and humanities or interdisciplinary teaching techniques are provided. The fifth section contains an outline for a one-semester chronological approach to humanities suitable for high school level. Three historical cultures--ancient China, classical Greece, and Renaissance Europe--are used to help students develop an appreciation for the impact of past cultures on the present. The sixth section contains an outline for an interdisciplinary two-semester course in high school American studies. Using a chrono-thematic approach, this course focuses on the theme of the American character. The seventh section details a one-semester thematic course in humanities. Drawing on art, music, literature, and music, the final section contains brief outlines of four thematic courses: the search for self, the individual and society, the future, and aging. (LP)
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: American Studies; Behavioral Objectives; Course Content; Curriculum Development; Curriculum Guides; Elementary Secondary Education; European History; Humanities Instruction; Interdisciplinary Approach; Resource Materials; Sequential Approach; Skill Development; Thematic Approach; United States History; China -- Greece -- Renaissance; Guides, Classroom -- Teacher